Learning to Teach Science: Elementary Teacher Candidates Facilitate Informal STEM Events. Issue 4 (2nd October 2018) - Dani, Danielle E.; Hartman, Sara L.; Helfrich, Sara R.
ABSTRACT: Facilitating successful informal STEM learning experiences is essential for building knowledge and comfort with STEM content for children and teachers alike. Informal learning experiences are by nature hands-on and interdisciplinary and provide play-based, real-world, authentic learning experiences. This article describes what elementary teacher candidates learn about teaching science from facilitating a STEM event within school settings and outside regular school hours. The article also presents implications for elementary-teacher education.